Resposta :
✥ O valor de Y = -11
--
Explicação passo-a-passo :
[tex] \\ { \large \displaystyle \sf {2(y+5) - (y - 1)=0 }}[/tex]
[tex]{ \large \displaystyle \sf {2y + 10 - y + 1 = 0 }}[/tex]
[tex]{ \large \displaystyle \sf {y + 10 + 1 = 0 }}[/tex]
[tex]{ \large \displaystyle \sf {y + 11= 0 }}[/tex]
[tex]{ \large \displaystyle \sf {y = 0 - 11}}[/tex]
[tex]{ \blue{ \boxed{ \boxed{ \pink{{ \large \displaystyle \sf {y = - 11}}}}}}} \\ \\ [/tex]
➡️ Então, teremos como resposta :
[tex] \\ { \blue{ \boxed{ \boxed{ \pink{{ \large \displaystyle \sf {y = - 11}}}}}}} \\ [/tex]